CREATING A FRIENDLY SCHOOL LEARNING ENVIRONMENT FOR NIGERIAN CHILDREN - Oluremi, Olaleye Florence (European Scientific Journal, ESJ, 2012)
This study evaluates the school learning environment in Nigerian’s primary schools. Areas of study include, classroom environment, provision of infrastructural facilities, Teacher/Pupils interaction in the classroom setting. The descriptive research design of the survey type was used, questionnaire tagged (CFV) “Child friendly environment was the instrument used to elicit information from the respondents. The population of the study consisted of all the teachers in the public primary schools in Osun State Nigeria. Sample comprised 250 teachers from selected Secondary Schools in the state. Data were collected using frequency counts means and percentages. Results showed that 25% of the selected schools were not child friendly. This was because they lacked infrastructural facilities such as toilet facilities, chairs, desks and tables. Most classrooms were not friendly to pupils with disabilities. Based on the findings, it was recommended that all education stakeholders in the primary education sector should made classroom environment attractive and pleasant for pupils. This would enhance teaching and learning and improve teacher productivity.